Disentangling orbital and spin exchange interactions for Co2+ on a rocksalt lattice - Sarte, P; Cowley, R; Rodriguez, E; Pachoud, E; Le, D; García-Sakai, V; Taylor, J; Frost, C; Prabhakaran, D; Macewen, C; Kitada, A; Browne, A; et al. (American Physical Society, 2018)
Neutron spectroscopy was applied to study the magnetic interactions of orbitally degenerate Co2+ on a host MgO rocksalt lattice where no long-range spin or orbital order exists. The paramagnetic nature of the substituted monoxide Co0.03Mg0.97O allows for the disentanglement of spin exchange and spin-orbit interactions. By considering the prevalent excitations from Co2+ spin pairs, we extract seven exchange constants out to the fourth coordination shell. An antiferromagnetic next-nearest-neighbor 180◦ exchange interaction is dominant; however, dual ferromagnetic and antiferromagnetic interactions are observed for pairings with other pathways. These interactions can be understood in terms of a combination of orbital degeneracy in the t2g channel and the Goodenough-Kanamori-Anderson rules. Our work suggest that such a hierarchy of exchange interactions exists in transition-metal-based oxides with a t2g orbital degeneracy.